IL-22 Mediates Host Defense against an Intestinal Intracellular Parasite in the Absence of IFN-γ at the Cost of Th17-Driven Immunopathology - Stange, Jörg; Hepworth, Matthew R; Rausch, Sebastian; Zajic, Lara; Kühl, Anja A; Uyttenhove, Catherine; Renauld, Jean-Christophe; Hartmann, Susanne; Lucius, Richard (The Journal of immunology (1950), 2012)
The roles of Th1 and Th17 responses as mediators of host protection and pathology in the intestine are the subjects of intense research. In this study, we investigated a model of intestinal inflammation driven by the intracellular apicomplexan parasite Eimeria falciformis. Although IFN-γ was the predominant cytokine during E. falciformis infection in wild-type mice, it was found to be dispensable for host defense and the development of intestinal inflammation. E. falciformis-infected IFN-γR−/− and IFN-γ−/− mice developed dramatically exacerbated body weight loss and intestinal pathology, but they surprisingly harbored fewer parasites. This was associated with a striking increase in parasite-specific IL-17A and IL-22 production in the mesenteric lymph nodes and intestine. CD4+ T cells were found to be the source of IL-17A and IL-22, which drove the recruitment of neutrophils and increased tissue expression of anti-microbial peptides (RegIIIβ, RegIIIγ) and matrix metalloproteinase 9. Concurrent neutralization of IL-17A and IL-22 in E. falciformis-infected IFN-γR−/− mice resulted in a reduction in infection-induced body weight loss and inflammation and significantly increased parasite shedding. In contrast, neutralization of IL-22 alone was sufficient to increase parasite burden, but it had no effect on body weight loss. Treatment of an E. falciformis-infected intestinal epithelial cell line with IFN-γ, IL-17A, or IL-22 significantly reduced parasite development in vitro. Taken together, to our knowledge these data demonstrate for the first time an antiparasite effect of IL-22 during an intestinal infection, and they suggest that IL-17A and IL-22 have redundant roles in driving intestinal pathology in the absence of IFN-γ signaling.